Optimizing Healthcare Delivery: A Comprehensive Guide to Workflow Models and Digital Transformation - Reshma Vemula (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article explores the transformation of healthcare delivery through advanced workflow models and digital solutions, emphasizing the critical role of technology integration in modern healthcare systems. The article examines various aspects of healthcare workflow optimization, including clinical processes, administrative workflows, patient engagement systems, and cross-departmental coordination. It shows the implementation of digital healthcare solutions, focusing on Electronic Health Records (EHR) interoperability, telemedicine advancements, mobile health applications, and patient portal development. The article analyzes process optimization and automation strategies, highlighting the significance of artificial intelligence, machine learning, and data analytics in healthcare operations. Through detailed examination of implementation best practices, the article addresses staff training, change management, technology integration, risk mitigation, and quality assurance methods. The article concludes with an evaluation of measuring impact and future directions, providing insights into key performance indicators, success metrics, and emerging technologies in healthcare delivery systems. This holistic approach to healthcare workflow optimization offers valuable insights for healthcare organizations seeking to enhance operational efficiency, improve patient care, and adapt to evolving technological landscapes.